ANALISIS DIGITAL MARKETING DALAM MENINGKATKAN VOLUME PENJUALAN PENGRAJIN BEKA BULUH DI KECAMATAN KABANJAHE KABUPATEN KARO - Prasektiyo, Agung; Yafiz, Muhammad; Dharma, Budi (Jurnal Ilmiah Ekonomi Dan Bisnis, 2024)
This research is motivated by the importance of marketing strategies through digital marketing to survive in competition between business actors. Therefore, business actors must be able to master digital marketing. This researcher aims to find out how the influence of digital marketing on increasing sales volume in reed beka craftsmen in Kabanjahe District, Karo Regency in using social media as a marketing tool. This study was an observational descriptive study, using primary data obtained based on interviews. The data obtained are analyzed using descriptive statistics and qualitative analysis and displayed in tabular form. The subjects in this study are owners, craftsmen and several related parties. The results showed that beka buluh craftsmen in Kabanjahe District, Karo Regency who have used digital marketing through social media as a means to market their products, experienced an increase in sales volume. This research shows that the use of digital marketing is very influential in competition between businesses and can increase sales volume.